2023
DOI: 10.1111/cge.14312
|View full text |Cite
|
Sign up to set email alerts
|

Variants of LRP2, encoding a multifunctional cell‐surface endocytic receptor, associated with hearing loss and retinal dystrophy

Abstract: Hereditary deafness and retinal dystrophy are each genetically heterogenous and clinically variable. Three small unrelated families segregating the combination of deafness and retinal dystrophy were studied by exome sequencing (ES). The proband of Family 1 was found to be compound heterozygous for NM_004525.3: LRP2: c.5005A > G, p.(Asn1669Asp) and c.149C > G, p.(Thr50Ser). In Family 2, two sisters were found to be compound heterozygous for LRP2 variants, p.(Tyr3933Cys) and an experimentally confirmed c.7715 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Lrp2, Igf1, and Dclk1 were downregulated in the whole cochlea of aging mice [ 24 ], which is consistent with the findings of He et al [ 32 ] that Igf1 is downregulated in aging mouse hair cells. Lrp2 is expressed enormously in the MC in mouse cochlea and this was identified by smFISH, single-cell and single-nucleus RNAseq in 2023 [ 33 ]. Padi2 and Gas2 were found to be downregulated in the vasculature of cisplatin-treated mice [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lrp2, Igf1, and Dclk1 were downregulated in the whole cochlea of aging mice [ 24 ], which is consistent with the findings of He et al [ 32 ] that Igf1 is downregulated in aging mouse hair cells. Lrp2 is expressed enormously in the MC in mouse cochlea and this was identified by smFISH, single-cell and single-nucleus RNAseq in 2023 [ 33 ]. Padi2 and Gas2 were found to be downregulated in the vasculature of cisplatin-treated mice [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, among female-biased genes across taxa, SLC6A2 overlapped between R. pusillus and R. sinicus, which is one of the ADHD risk genes in humans and has also been identified to have sexually dimorphic effects with a greater effect on females than on males [65]. Another notable gene is LRP2 overlapped between R. pusillus and R. affinis hainanus, which was identified as a deafness gene [66,67] as well as a candidate echolocation gene associated with the origin of laryngeal echolocation in bats [60]. A previous study also showed that LRP2 can partially mediate a female-specific effects of LCN2 on metabolic traits in mice [68].…”
Section: Discussionmentioning
confidence: 99%